2009
DOI: 10.1128/aac.01540-08
|View full text |Cite
|
Sign up to set email alerts
|

Tetracyclines Modulate Protease-Activated Receptor 2-Mediated Proinflammatory Reactions in Epidermal Keratinocytes

Abstract: In addition to their antibiotic effects, tetracyclines have anti-inflammatory action that is often beneficial in the control of inflammatory skin disorders. In this study, we examined the effects of tetracycline (TET) and two of its derivatives, doxycycline (DOX) and minocycline (MIN), on the production of interleukin-8 (IL-8) elicited by the activation of protease-activated receptor 2 (PAR2) in normal human epidermal keratinocytes (NHEK). In NHEK, the production of IL-8 stimulated by an agonist peptide of PAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 34 publications
(39 reference statements)
1
44
0
2
Order By: Relevance
“…This may have contributed to the increased skin permeation of tetracycline. This antibiotic drug possesses anti-inflammatory activity with various skin disorders [45]. Drugs that reveal excessive hydrophilicity such as tetracycline (log P = À2.6) have no optimal transport route into the skin, and the SC is the predominant barrier.…”
Section: Discussionmentioning
confidence: 99%
“…This may have contributed to the increased skin permeation of tetracycline. This antibiotic drug possesses anti-inflammatory activity with various skin disorders [45]. Drugs that reveal excessive hydrophilicity such as tetracycline (log P = À2.6) have no optimal transport route into the skin, and the SC is the predominant barrier.…”
Section: Discussionmentioning
confidence: 99%
“…It also inhibits apoptosis and oxygen species release, and decreases neutrophil migration [7]. Furthermore, doxycycline attenuates the protease-activated receptor 2/interleukin 8 axis in keratinocytes and thereby effectively modulates the pro-inflammatory response in the skin [8]. Other therapeutical options include repetitive punctures [5], local injection of steroids [1,4] and surgical excision [2].…”
Section: Discussionmentioning
confidence: 99%
“…Ishikawa et al (2009) reported that minocycline, at concentrations similar to those obtained therapeutically in serum (5 or 10 mM) (Agwuh and MacGowan, 2006), reduced the protease-activated receptor 2-mediated production of IL-8, and thus attenuated the proinflammatory process in epidermal keratinocytes. They proposed that the ability of tetracyclines to chelate Ca 2+ may contribute to these effects, as protease-activated receptor 2 activation transiently increases intracellular Ca 2+ levels in keratinocytes, triggering the downstream binding of NF-kB to DNA (Macfarlane et al, 2005;Stefansson et al, 2008).…”
Section: Effects Of Minocycline On Dermatitismentioning
confidence: 99%